The effects of foreign direct investment on job stability: Upgrades, downgrades, and separations - Linda Borrs; Johann Eppelsheimer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
We use linked employer-employee data to estimate the effect of foreign direct investment (FDI) on workers' job stability. We are the first to consider firm-internal job transitions. Specifically, we examine the impact of FDI on the individual likelihood to up- or downgrade to occupations with more or less analytical and interactive tasks. To do so, we propose an iterative matching procedure that generates a homogeneous sample of firms with equal probabilities of investing. Based on this sample, we use proportional hazard models to retrieve dynamic effects on workers. We find that FDI increases the likelihood of up- and downgrades by 25 and 37 percent, respectively. These effects increase with the share of non-routine and interactive tasks and become measurable two years after the investment. FDI does not increase the hazard of the separation of workers and firms. Instead, there is a temporal lock-in effect after the investment. Our results highlight the importance of firm-internal restructuring as a channel for adjusting to altered labor demand in response to FDI. – – Wir untersuchen die Auswirkungen von ausländischen Direktinvestitionen (FDI) auf die Beschäftigungstabilität von Arbeitnehmerinnen und Arbeitnehmern mittels Sozialversicherungsdaten. Erstmalig berücksichtigen wir hierbei unternehmensinterne Jobwechsel und untersuchen die Effekte von FDI auf die individuelle Wahrscheinlichkeit von Up- oder Downgrades hin zu Berufen mit mehr oder weniger analytischen und interaktiven Tätigkeiten. Zu diesem Zweck entwickeln wir ein iteratives Matching-Verfahren, welches einen homogenen Datensatz von Firmen mit gleichen Investitionswahrscheinlichkeiten erzeugt und berechnen dynamische Effekte mit Proportional Harzardmodellen. Unsere Ergebnisse zeigen, dass FDI die Wahrscheinlichkeit von Up- und Downgrades um 25 bzw. 37 Prozent erhöht. Diese Effekte nehmen mit dem Anteil an nicht-routine und interaktiven Tätigkeiten zu und werden zwei Jahre nach der Investition messbar. FDI erhöht nicht die Wahrscheinlichkeit von Trennungen von Beschäftigten und Unternehmen. Stattdessen führt FDI zu einem temporären Lock-in-Effekt. Unsere Befunde belegen die Bedeutung von firmeninternen Umstrukturierungen als Reaktion auf eine veränderte Arbeitsnachfrage durch FDI.
Keywords: F16; F23; F66; J23; J62; 330; FDI; job stability; multinational firms; tasks